Técnicas fisioterapéuticas para tratar la kinesiofobia de pacientes post ruptura de ligamento cruzado anterior - Juan Pablo, Ramón Aguirre (2020)
The research was focused on the bibliographic review modality, making the main objective to characterize the physiotherapeutic techniques to treat kinesiophobia in patients post rupture of the Anterior Cruciate Ligament, determining the effectiveness of the techniques in the physical and psychological area of the patient during their recovery process to reduce the kinesiophobic index, the importance of the application, evaluation and work with physiotherapeutic techniques in the aforementioned areas is highlighted in order to improve the quality of life and physical condition after surgery. The aforementioned physiotherapeutic techniques to treat kinesiophobia are not well known in the workplace, due to the lack of scientific articles based on the subject, which confirm this; Despite the little information that is offered online, 75 scientific articles with publication dates from 2007 to 2019 could be found, mostly from bibliographic sources such as: Scielo, PubMed, El sevier and Google Scholar. Using the exclusion and evaluation criteria on the PEDro scale, the articles that were considered suitable for the study were 35, since they met with a score equal to or greater than 6 on the PEDro scale; Of these 35 articles, some are in languages such as English, and mostly in Spanish. When concluding with the respective investigation after analyzing the different authors, the proposed objective could be completed, characterizing the physiotherapeutic techniques to treat kinesiophobia in patients after rupture of the Anterior Cruciate Ligament.